A wrongful death - Wilhelm, Kate (Wilhelm, Kate. Barbara Holloway novels., 2007)
Barbara's peace at her retreat on the Oregon coast is shattered when a terrified young boy leads her to a cabin in the woods where his battered mother has clearly been left for dead. Barbara runs for help, but by the time she returns both mother and son are gone.